Contesting 'race' and sport : shaming the colour line - Hylton, Kevin (London : Routledge, 2017)
"In the decade since Kevin Hylton's seminal book 'Race' and Sport was published, racialised issues have remained at the forefront of sport and leisure studies. In this important new book, Hylton draws on original research in contemporary contexts, from sports coaching to cyberspace, to show once again that Critical Race Theory is a powerful tool for interrogating problematic social phenomena. Inspired by W.E.B. Du Bois' statement that "the problem of the twentieth century is the problem of the colour line", this book sheds a critical light on the way sport perpetuates racism, while identifying opportunities to challenge its insidious presence. "--Provided by publisher.
chapter 1 Critical race theory in sport / Kevin Hylton -- r Kevin Hylton -- r
Keywords: Discrimination in sports -- History -- 20th century; Racism in sports -- History -- 20th century; Sports -- Social aspects -- History -- 20th century